CASE STUDY OF ENHANCING THE EFFECTIVENESS OF FEMALE ASSOCIATION- AN EXAMPLE OF CHIAYI FEIYAN ENTREPRENEURS ASSOCIATION - Lu, Sho-Min; Lu, Te-Tsai (International Journal of Application on Economics and Business, 2024)
Women are increasingly assuming vital roles in the domestic industry, with numerous domestic organizations dedicated to assisting women in employment and entrepreneurship. The government has also allocated significant resources for guidance and support. The operational performance of these organizations reflects the tangible benefits of counseling and the influence of women in both the business and social spheres. This study employs qualitative research methods such as "case study," "in-depth interview," and "focus group interview," utilizing the "Balanced Scorecard, BSC" framework, with the Chiayi Feiyan entrepreneurship development association (EDA).as the case study. Through interviews, the study explores how to enhance the operational performance of women's organizations. Using the case study organization as an example, the research results in areas such as finance, operational processes, learning and growth, and customer relations can serve as a reference for other branches or similar organizations, aiming to improve the effectiveness of counseling for women's employment and entrepreneurship.